Evaluation of photodegradation in LDPE/modified starch blends - Flávia G. D. Ferreira (Polímeros, 2009)
Photodegradation of LDPE/modified starch blends 80/20 m/m has been examined by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and X ray diffraction (DRX) before and after exposure to ultraviolet radiation (UV). Samples were exposed to UV in the laboratory for periods of 6, 24, 48 and 60 hours. The main alteration in the polymeric material after exposure to the radiation was a decrease in the mechanical properties, tensile strength and elongation. There were also changes in the chemical structure of the blend with an increase in the carbonyl and vinyl indices, 65.58 and 53.29%, respectively. The analysis of the blend crystallinity pointed to the formation of a new crystalline symmetry that did not exist before the irradiation.